Food-grade cloning and expression system for Lactococcus lactis. - Platteeuw, C (1996)
A versatile set of cloning and expression vectors has been developed for application in self-cloning and other genetic modifications of Lactococcus lactis. The expression vectors were equipped with the controlled and strong lacA promoter of the lactococcal lactose operon. In addition, the transcriptional terminator of the aminopeptidase N gene, pepN, was inserted, which in some cases increased the genetic stabilities of the vectors and the cloned DNA. The small, 0.3-kb lacF gene encoding the soluble carrier enzyme IIALac was used as a dominant selection marker in the plasmid-free L. lactis strain NZ3000 carrying an in-frame deletion of the chromosomal lacF gene. Lactose-utilizing transformants were easily selected on lactose indicator plates at high frequencies and showed a copy number of approximately 50 plasmids per cell. All vectors were stably maintained in the lacF strain NZ3000 when grown on lactose, and only the high-level expression vectors showed some instability when their host was grown on glucose-containing medium. The application potentials of the expression vectors carrying the lacF marker were determined by cloning of the promoterless Escherichia coli gusA reporter gene under control of the lacA promoter followed by analysis of its expression. While in one of the vectors this resulted in a promoter-down mutation in the -10 region of the lacA promoter, in other vectors high-level and controlled expression of the gusA gene was observed.